The Polish-Lithuanian Commonwealth as “the Paradise for Jews”. A Myth or Reality? - Wijaczka, Jacek (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
In the literature on the history of Jews in the Polish-Lithuanian Commonwealth we quite frequently come across the reference to a saying about the early modern Poland–Lithuania as “the Paradise for Jews”. The saying about Poland as the Paradise for Jews, the hell for peasants and the purgatory for burghers was recorded first time at the beginning of the seventeenth century and has been a subject of research by many historians since a long time. However, the newest state of research allows us to reconsider the question, whether the Polish-Lithuanian Commonwealth was indeed “Paradise” for the Jewish communities living in the country. The author of this article also analyzes how the situation of the Jewish population was seen both by contemporary commentators in Poland–Lithuania as well as by foreign travellers.